PERBANDINGAN ELEKTRODA Fe-SS DAN Al-SS DALAM MENURUNKAN TSS DAN KEKERUHAN LIMBAH LAUNDRY MELALUI PROSES ELEKTROKOAGULASI - Novita, Diana Novita Sari (Journal of Research and Education Chemistry, 2026)
Laundry wastewater contains suspended solids and colloidal particles that lead to high levels of total suspended solids (TSS) and turbidity, which may cause environmental pollution if discharged without proper treatment. Electrocoagulation is a wastewater treatment method that utilizes the in situ formation of coagulants through electrochemical reactions at metal electrodes. This study aims to compare the performance of iron–stainless steel (Fe–SS) and aluminum–stainless steel (Al–SS) electrodes in reducing TSS and turbidity in laundry wastewater. Electrocoagulation experiments were conducted at laboratory scale using voltage variations of 1.5, 3, and 4.5 V with a contact time of up to 60 minutes under neutral pH conditions. The results show that increasing voltage and contact time improved the removal efficiency of both TSS and turbidity for both electrode configurations. Under optimum conditions (4.5 V and 60 minutes), the Fe–SS electrode achieved a TSS removal efficiency of 67.14% and a turbidity reduction of 54.55%, while the Al–SS electrode resulted in a TSS removal of 64.29% and a turbidity reduction of 62.68%. These differences are attributed to the characteristics of the generated coagulants during the electrocoagulation process. The Fe–SS electrode produces Fe(OH)3 flocs that are denser and heavier, making them more effective in settling suspended solids contributing to TSS. In contrast, the Al–SS electrode forms amorphous Al(OH)3​ with a larger surface area, which enhances the adsorption of fine colloidal particles responsible for turbidity. This study indicates that electrode selection influences the effectiveness of pollutant removal in laundry wastewater electrocoagulation. Keywords : electrocoagulation, Fe-SS, Al-SS, Total Suspended Solid, turbidity